Latency-associated peptide (LAP)+CD4+ regulatory T cells prevent atherosclerosis by modulating macrophage polarization - Yu, Jian (Clinical immunology (Orlando, Fla.), 2023)
Copyright © 2023. Published by Elsevier Inc.